Knowledge, attitude, and life concerns of urban poor parents not utilizing Barangay Day Care Center for preschool children - Laurel, Maxin B.
This study explored the parent's non-utilization of Barangay Day Care Center for their preschool children. Specifically, this study sought to determine the parents' life concerns, knowledge about child development, and awareness and attitude towards Barangay Day Care Center. Thirty parents with preschool children were chosen through purposive sampling and snowball from five areas of Barangay U.P. Campus. Qualitative and quantitative analysis through the exploration of the parents' responses during the interview and survey were employed. Results indicate that the factors which affected parents' non-utilization of Barangay Day Care Center were child's age and financial difficulties. But parents acknowledge the importance of Day Care Center and believed to enroll a child at age four or five. Parents spent time teaching their children school-related activities while they are home. Their life concerns include family wellness, education, financial especially daily food consumption, and moral guidance. Future studies may explore fathers' life concerns for family, and their views and attitudes towards the Day Care Service.